KURANGNYA PENGETAHUAN IBU TERHADAP KOMPLIKASI DIARE PADA BALITA DAN ANAK DI PUSKESMAS SUKORAME KEDIRI: LACK OF MOTHER'S KNOWLEDGE OF DIARRHEA COMPLICATIONS IN TODDLER AND CHILDREN AT SUKORAME KEDIRI HEALTH CENTER - Nofiah, Niafatun; Khofipah, Alfiyah Nur; Sirotujani, Ferdiyansyah (WELL BEING, 2024)
There is still little discussion about complications caused by diarrhea in the community, especially among mothers, so that many parents (mothers) do not know the impact of complications caused by diarrhea in toddlers (0-5) years and children (5-11) years. The purpose of this study was to determine the level of maternal knowledge about the complications of diarrhea in toddlers and children. This study is a survey analytic study with a cross sectional approach, the sample in this study were mothers who have toddlers 0-5 years and children 5-11 years affected by diarrhea. The sampling technique used accidental sampling and obtained 59 respondents. The results showed that the majority of respondents had a lack of knowledge as many as 37 respondents (63%), sufficient knowledge 12 respondents (20%), and good knowledge 10 respondents (17%). The conclusion of this study It is very important to provide education to parents (mothers) about the complications of diarrhea that can be experienced by toddlers and children.